Evaluation of recurrent esophageal variceal rupture post-endoscopic band ligation: A case report - Tasya Fabiola Alim (Malahayati International Journal of Nursing and Health Science, 2025)
Background: One serious side effect of portal hypertension that is often seen in individuals with liver cirrhosis is esophageal varices.  Even after Endoscopic Band Ligation (EBL), there is a significant chance that these varices may bleed again.  Uncontrolled portal pressure, therapeutic noncompliance, and concomitant gastrointestinal disorders are often linked to rebleeding. Purpose: To evaluate the risk factors influencing the success of Endoscopic Band Ligation (EBL) in preventing rebleeding in patients with a history of esophageal variceal rupture. Method: Using a descriptive case study approach with an eye on one patient undergoing treatment at a hospital, this research medical records provided data, which were then descriptively examined to assess clinical factors, forms of treatment given, and patient condition over time. Results: Results revealed that individuals with hepatic cirrhosis brought on by a hepatitis B infection are very likely to rebleed. Among the contributing causes were uncontrolled portal hypertension, congestive gastropathy, gastrointestinal bleeding-related chronic anemia, and inadequate therapeutic adherence. Furthermore important were eating behaviors that aggravate gastrointestinal problems. Conclusion: Stopping rebleeding calls for a multidisciplinary strategy. Monitoring portal pressure, following beta-blocker and antiviral treatment, and teaching patients about long-term care are among these aspects. To confirm these results, further research using bigger sample sizes is required.